2021
DOI: 10.1002/brb3.2268
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis identify significant relationships between clinical anxiety and lower urinary tract symptoms

Abstract: Background: Lower urinary tract symptoms (LUTS), such as voiding symptoms, overactive bladder, and interstitial cystitis, and anxiety disorders are often comorbid conditions in patients. However, the existing evidence regarding the rates and nature of the co-occurrence of these conditions has not been systematically evaluated. The aim of this study was to examine these relationships. Methods:We conducted a systematic review and meta-analysis to examine the relationship between LUTS and anxiety. We searched for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
0
10
0
1
Order By: Relevance
“…24 Kaur et al 25 found depression in all 100 patients with UI who participated in their study. In the systematic review of Mahjani et al, 26 it was emphasized that there is a clinically significant relationship between LUTS and anxiety. In the findings of another study, it was said that there was a bidirectional relationship between LUTS and anxiety/depression.…”
Section: Discussionmentioning
confidence: 99%
“…24 Kaur et al 25 found depression in all 100 patients with UI who participated in their study. In the systematic review of Mahjani et al, 26 it was emphasized that there is a clinically significant relationship between LUTS and anxiety. In the findings of another study, it was said that there was a bidirectional relationship between LUTS and anxiety/depression.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review reported an association between LUTS and psychiatric symptoms in a broad sense, however, most studies report on LUTS in association with depression and anxiety, and fewer studies report on other psychiatric symptoms or disorders 53 …”
Section: Optimizing Adherence To Self‐catheterizationmentioning
confidence: 99%
“…Hay evidencia que sugiere que la ansiedad y la depresión pueden estar correlacionadas con las enfermedades del tracto urinario inferior 15 . Un estudio realizado en Taiwán por Chung et al 16 muestra que los pacientes con CI tienen más prevalencia de comorbilidad y que los participantes de la muestra tenían 4,37 veces más probabilidades de tener un diagnóstico previo de trastorno de ansiedad.…”
Section: Ansiedad Y Depresiónunclassified